Keefektifan Model Pembelajaran PACE Berbantuan Google Classroom terhadap Kemampuan Penalaran Matematis Siswa pada Materi Phytagoras - Rahmi, Miftah Fathur; Dewi, Nuriana Rachmani; Wijayanti, Kristina (Universitas Cokroaminoto Palopo, 2024)
Reasoning is a very important aspect of mathematical ability in learning mathematics. Mathematical reasoning ability is not optimal, one of which is learning that does not involve students enough. One of the learning models that encourages students to be active in the learning process is the PACE model. The aim of this research is to determine the effectiveness of PACE learning assisted by Google Classroom on students' mathematical reasoning abilities. This research uses a quantitative approach with a quasiexperimental research design and the form used is the nonequivalent pretest-posttest control group design. In this design there are two groups selected randomly (cluster random sampling).The data collection techniques used are test techniques and observation techniques. Based on research results, PACE learning assisted by Google Classroom is effective for mathematical reasoning abilities. This can be seen from the obtained which is greater than , so is rejected. This means that the results of the mathematical reasoning ability test of students using Pythagorean material who used PACE learning assisted by Google Classroom completed classical learning. Then we get so is rejected. This means that the proportion of students who complete learning with PACE learning assisted by Google Classroom is more than the proportion of students who complete learning with Problem Based Learning (PBL). Apart from that, we get then is rejected. This means that the average mathematical reasoning ability of students using PACE learning assisted by Google Classroom is more than the average mathematical reasoning ability using PBL. And obtained then is rejected. This means that the average mathematical reasoning ability after being subjected to PACE learning assisted by Google Classroom is better than the mathematical reasoning ability of students before being subjected to PACE learning assisted by Google Classroom.